Hemifacial Spasm Treated by Thread-embedding Therapy - Jae-eun Jung; Na-Young Jo; Jeong-Du Roh (MEDrang Inc., 2019)
The aim of this study was to investigate the efficacy of treatment with thread-embedding therapy for 24 patients with hemifacial spasm (HFS). The muscle spasm of these patients was treated with threadembedding therapy. Patients with nuchal pain were treated with tendino-musculature acupuncture in the sternocleidomastoid, splenius, and trapezius muscles. We evaluated the treatment effect using the Scott's scale, where 20, 3, 1, and 0 patients presented Scott's grade 0, grade 1, grade 2, and grade 3, respectively. The grade of the spasm intensity decreased noticeably after treatment. The results revealed that the Scott's grade changed to 0 in 83.3% of HFS patients, and 91.7% patients felt satisfied with thread-embedding therapy. These findings suggested that thread-embedding therapy was effective and can be used widely for HFS.